Autophagy Induced by the Withdrawal of Mitogens Promotes Neurite Extension in Rat Neural Stem Cells. Issue 7 (22nd May 2013) - Chen, Ye; Zhao, Lu; Tian, Xiaowei; Liu, Tingting; Zhong, Jiateng; Sun, Liankun; Liu, Jiamei
ABSTRACT Neural stem cells (NSCs) are usually affected by a number of biological functions in neural traumatic and degenerative diseases. Autophagy may be involved in these diseases. However, whether autophagy could affect NSCs is largely unknown. Therefore, we aimed to investigate intracellular microstructures, proliferation, axon extension, and Beclin‐1 expression of rat NSCs by basic culture medium and conditioned medium without epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF). Transmission electron microscopy showed the formation of autophagic vacuoles in conditioned medium. Compared to the control group with normal medium, the number of secondary neurosphere was significantly reduced whereas the expression of Beclin‐1 was enhanced. The majority of NSCs were nestin‐positive when EGF/bFGF was withdrawn for 3 days and showed enhanced neurite extension, which was suppressed by autophagy antagonist 3‐methyladenine. Our findings revealed that a short‐term paucity of mitogens in microenvironments could induce autophagy of NSCs, which facilitated NSCs' axonal growth. © 2013 Wiley Periodicals, Inc. J BiochemMol Toxicol 27:351‐356, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/jbt.21496